Menciptakan Lingkungan Belajar yang Menyenangkan untuk Meningkatkan Keaktifan Siswa Kelas III SDN Gempol Kolot 2 - Jejen Tabriji (Universitas Palangka Raya, 2025)
This study aims to create a fun learning environment to increase student activity in the third grade at SDN Gempol Kolot 2. The study used a classroom action research method with two cycles. Each cycle consists of planning, implementation, observation, and reflection stages. The results showed a significant increase in student activity after the implementation of more fun and interactive learning. In the first cycle, student participation in class discussions was only 60%, while in the second cycle it increased to 85%. Involvement in group activities also increased from 65% to 90%, and responses to learning materials increased from 55% to 80%. Additionally, students showed an increase in the desire to ask questions, rising from 50% to 75%. This study concludes that a fun learning environment can enhance student activity, positively influencing the quality of learning.